ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT MENABUNG DI BANK PADA KALANGAN PELAJAR (Studi Kasus Pada Pelajar SMP Negeri 3) - Achmad Rudzali; Rahmawati Fitriana; Mat Juri; Renny Augustini Putri (Politeknik Negeri Samarinda, 2020)
This study aims to determine the effect of knowledge factors, location factors and pocket money factors on interest in saving among students of Sebulu 3 Public Middle School. The statistical tool used in this study is multiple linear regression. This research uses quantitative methods. The data analysis technique used in this study is the validity test, reliability test, normality test, multicollinearity test and heteroscedasticity test. While the hypothesis test uses the T test, F test and R2 test, using an analysis tool, the SPSS 21 program. The object of the research is students of SMP Negeri 3 Sebulu with a sample of 158 students. The data of this study uses data collection techniques by observing and distributing questionnaires.Keywords: knowledge factor, location factor, pocket money factor, saving interest.